The serum cholesterol level of choledocholithiasis patients was significantly lower than that of healthy people - Li, Linzhen; Hu, Tulan; Wang, Di (Frontiers in Endocrinology, 2025)
Background and purposeThe specific pathogenesis of choledocholithiasis is still unclear. The objective of this study was to investigate whether serum cholesterol level is related to the incidence of choledocholithiasis.Patients and methodsA total of 169 choledocholithiasis patients were include in this study. We investigated whether total cholesterol (TC), triglyceride (TG), high density lipoprotein (HDL-C), low density lipoprotein (LDL-C), TC/TG, LDL-C/HDL-C in choledocholithiasis patients differed from that in healthy people.ResultsThere were 64 male and 105 female patients. There were significant differences in TC (P<0.001), TG (P=0.006), HDL-C (P<0.001) and LDL-C (P=0.001) between the two groups. The TC, TG, HDL-C, LDL-C in the choledocholithiasis patients group were significantly lower than that in the healthy population. In the subgroup analysis, we further investigate whether above parameters in choledocholithiasis patients differed from that in healthy people by gender. There was no significant difference in TG (P=0.182), TC/TG (P=0.982), LDL-C/HDL-C (P=0.392) between the male choledocholithiasis patients group and the male healthy population group. There were significant differences in TC (P=0.001), HDL-C (P=0.014) and LDL-C (P=0.026) between the two groups. There were no significant difference in TC/TG (P=0.590), LDL-C/HDL-C (P=0.116) between the female choledocholithiasis patients group and the female healthy population group. There were significant differences in TC (P<0.001), TG (P=0.016), HDL-C (P<0.001) and LDL-C (P=0.009) between the two groups.ConclusionsThe serum TC, HDL-C and LDL-C in choledocholithiasis patients were significantly lower than those in healthy people.